Pelatihan Penggunaan Software 3D Sketchup untuk meningkatkan Kreatifitas Pemuda Jinontro - Jawwad Sulthon Habiby; Yoyok Winardi; Ghulam Asrofi Buntoro; Munaji Munaji; Nur Wahid Khoirul Anwar (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2024)
Youth need to form their identity as the nation's successor, one of which can be done by participating in a self-development activity, both within the internal scope of the youth group and outside the youth group. The Jinontro Youth Group has several activities, one of which is called the Youth Creativity Improvement Program, which can shape the basic character of youth, namely the character of leadership, solidarity, loyalty, kinship, education, and responsibility. In order to improve character building, a training is proposed for the Jinontro Youth Group entitled